Individual and Social Predictors of Prosocial Behavior among Chinese Adolescents in Hong Kong - Lai, Frank H. Y.; Siu, Andrew M. H.; Shek, Daniel T. L. (Frontiers in Pediatrics, 2015)
Based on the human ecological model, this study hypothesized that individual competence in empathy, prosocial moral reasoning, and social influence from parents, peers, and school are the key determinants of prosocial behaviour among Chinese adolescents in Hong Kong. We recruited a sample of high school students who engaged in volunteering activities regularly (N = 580). They completed a self-administrated questionnaire designed to measure prosocial behaviour and its hypothesized predictors using a number of standardized instruments. The results of multiple regression show that social influence factors, including peer, school, and parent influence, are strong predictors of helping intention and prosocial behaviour, while individual competence factors like empathy and prosocial moral reasoning are not. Male participants had higher empathy scores and helping intention than males, perceived their parents as more helpful, and their schools as more supportive of prosocial behaviour. However, the significant predictors of prosocial behaviour and helping intention were similar across gender. The findings indicate that social influence is strongly linked to prosocial behaviour. This implies that socialization and social support for prosocial norms and behaviour can exert a powerful influence on the behaviour of young people in a Chinese population.